A Chinese herb preparation, honokiol, inhibits Streptococcus mutans biofilm formation. (March 2023) - Ren, Shirui; Yang, Yingming; Xia, Mengying; Deng, Yalan; Zuo, Yuling; Lei, Lei; Hu, Tao
Abstract: Objective: This study aimed to investigate the antibiofilm and anticariogenic effects of honokiol, a traditional Chinese medicine, on the cariogenic bacterium Streptococcus mutans ( S. mutans ). Design: The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of honokiol on S. mutans UA159 were measured. Then, S. mutans were treated with honokiol at concentrations of 1/2 MIC and 1/4 MIC. Extracellular polysaccharide (EPS) synthesis was assessed with confocal laser scanning microscopy (CLSM) and the anthrone–sulfuric method. Crystal violet staining and scanning electron microscopy (SEM) were used to demonstrate the characteristics and morphology of S. mutans biofilms. Colony-forming unit (CFU) assay was performed to observe the antibacterial effect of honokiol. Lactic acid production of 24-h biofilms was measured by the lactic acid assay. The expression level of caries-related genes ( gtfB/C/D, comD/E and ldh ) was identified by quantitative real-time PCR (qRTPCR) to explore the relevant mechanism. And the cytotoxic effect on human gingival fibroblasts (HGFs) was evaluated by the Cell Counting Kit-8 (CCK-8) assay. Results: The MIC and MBC of honokiol on S. mutans were 30 μg/mL and 60 μg/mL, respectively. Honokiol inhibited biofilm formation, EPS synthesis and lactic acid production. It also decreased the expression of glucosyltransferases (Gtfs) and quorum sensing (QS) system encoding genes. Moreover, honokiol showed favorable biocompatibility with HGFs. Conclusions: Honokiol has an inhibitory effect on S. mutans and favorable biocompatibility, with application potential as a novel anticaries agent. Highlights: Honokiol exhibits anti-biofilm effect on Streptococcus mutans . Honokiol inhibited the cariogenic properties of Streptococcus mutans . Honokiol decreased the expressions of gtf genes, com D/E and ldh . Honokiol has the potential to be developed for prevent caries.